Evaluating ex situ rates of carbon dioxide flux from northern Borneo peat swamp soils. (18th January 2022) - Adamczyk, Bartosz; Low Ying Si, Eliza; Chadwick, Michael A.; Smith, Thomas E. L.; Sukmaria Sukri, Rahayu
Abstract: This study quantified CO2 emissions from tropical peat swamp soils in Brunei Darussalam. At each site, soil was collected from areas of intact and degraded peat and CO2 flux, and total organic content were measured ex situ. Soil organic content (~20–99%) was not significantly different between intact and degraded forest samples. CO2 flux was higher for intact forest samples than degraded forest samples (~1.0 vs. ~0.6 μmol CO2  m −2  s −1, respectively) but did not differ among forest locations. From our laboratory experiments, we estimated a potential emissions of ~10–20 t CO2  ha −1  y −1 which is in the lower range of values reported for other tropical peat swamps. However, our results are likely affected by unmeasured variation in root respiration and the lability of resident carbon. Overall, these findings provide experimental evidence to support that clearance of tropical peat swamp forests can increase CO2 emissions due to faster rates of decomposition.